PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN OPINI AUDITOR TERHADAP AUDIT DELAY - Armansyah, Fendi; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of firm size, profitability and auditor opinion to the audit delay. The samples are 34 property and real estate companies which are listed in Indonesia Stock Exchange in 2012-2014 periods. The sample collection technique has been done by using purposive sampling method. The data is the secondary data. Prerequisite analysis test which includes normality test, multicolinearity test, heteroscedaticity test and autocorrelation test has been conducted first before the data analysis. The data analysis is done by using multiple linear regressions analysis. The result of the research shows that firm size has significant influence to the audit delay. It indicates that firm size will have an influence to the speed of presenting financial statement to the public. Profitability does not have any influence to the audit delay. It indicates that the ability of the company to generate profit does not have any significant influence to the time period of the delivery of audited financial statement. The auditor opinion has significant influence to the audit delay. It indicates that when the opinion which has been received by the company is getting worse, the audited financial statement will be long to be published.Keywords: firm size, profitability, auditor opinion, audit delay